Importance of Developing Strength Endurance in Archers - Radičević, Miljan; Čolović, Miljko; Milosavljević, Srđan (Sport - nauka i praksa, 2025)
Success in archery depends on numerous factors, one of the fundamental ones being an archer's ability to achieve a high level of focus and consistency over an extended period during competitions. This is primarily achieved through one of the four defined aspects of archery — physical fitness, specifically well-designed and tailored strength endurance exercises. The first goal of this analysis is to highlight the extent of exertion, the significance, and the essential need for strength endurance in archers. The second goal is to present a methodology for achieving the necessary level of physical fitness, particularly strength endurance in archers. It is anticipated that by assessing an archer's initial physical fitness level and then applying exercises designed to develop the required strength endurance, including "SPT" (Specific Physical Training) for endurance, strength/force, flexibility, and structure, as well as "modality" exercises, an archer's abilities will be enhanced. This analysis, based on a review of literature and expert opinions, incorporates experience from working with archers, as well as insights from foreign coaches obtained through lectures, seminars, published papers, or books. Based on the exercises and methodology used in this paper, it is assumed that they will contribute to improving an archer’s abilities in the training process, ultimately leading to better performance results.
Keywords: strength endurance; SPT; archery; physical fitness